UPAYA MENINGKATKAN HASIL BELAJAR PKn MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE NHT (NUMBERED HEAD TOGETHER) PADA SISWA KELAS XI IPA 3 SMA NEGERI 3 SINGARAJA TAHUN AJARAN 2012/2013 - WIDYASARI, NI LUH (Universitas Pendidikan Ganesha, 2013)
ABSTRACTThis study aims to improve learning outcomes Citizenship Education (Civics)through the application of learning models NHT (Numbered Head Together). Thisresearch is a class act that is done in two cycles of action. Stages-tahapn in eachcycle is the planning, implementation, observation / evaluation and reflection. Thesubjects were students of class XI IPA 3 SMA Negeri 3 Singaraja, amounting to36 people. The object includes learning outcomes Civics. The data were collectedusing observation techniques, giving tests, and questionnaires. Observationtechniques used to collect data on students in participating in learning activitiesCivics. Giving tests are used to obtain data on student learning outcomes Civics.Questionnaires were used to collect data related to the application of the methodin learning NHT. Furthermore, the data collected were analyzed by descriptivequantitative. The results of this study indicate that the application of learningmodels NHT (Numbered Head Together) in a Civics lesson in class XI IPA 3SMA Negeri 3 Singaraja, can improve learning outcomes Civics. It can be seenfrom the following data: 1) an increase in the average value of the learningoutcomes Civics cycle of 69.4 to 75.3% absorption of mastery learning classicalscore of 69.44%, while the average yield on learning Civics second cycle is equalto 81.25% with the absorption of 81.3 94.44% mastery learning classical. Fromcycle I to cycle II Civics increase student learning outcomes.Key Words: Cooperative Learning, Model Type NHT (Numbered HeadsTogether), student learning outcomes,Learning Civics.